Effectiveness of Cognitive Conflict-Based Teaching Material Integrated with Augmented Reality in Improving Students’ Conceptual Understanding and Self-Efficacy on Light Waves - Intan Ayu Tresna; Fatni Mufit; Ratnawulan Ratnawulan; Selma Riyasni (Jurnal Penelitian Pembelajaran Fisika, 2026)
Effective physics learning should enable students to develop sound conceptual understanding and strong self-efficacy to solve scientific problems. Physics learning on light waves remains challenging due to students’ low conceptual understanding, misconceptions, and low self-efficacy caused by abstract concepts and teacher-centered instruction. These challenges highlight the need for innovative teaching materials. This study aimed to investigate the effectiveness of Augmented Reality (AR)-integrated cognitive conflict-based teaching materials in improving students’ conceptual understanding and self-efficacy. A quasi-experimental study employing a nonequivalent pretest–posttest control group design was conducted with 36 experimental and 33 control class students at SMA Negeri 1 Batusangkar. Data from a validated four-tier diagnostic test and self-efficacy questionnaire were analyzed using descriptive statistics, Mann–Whitney U, and Independent Sample t-tests. Results showed the experimental class's correct understanding increased from 26% to 80%, while misconceptions decreased from 40% to 8%. Statistical analysis revealed significant differences in conceptual understanding (p < .001) and self-efficacy (p < .001) between classes. These findings demonstrate that AR-integrated cognitive conflict-based materials effectively enhance both cognitive and affective outcomes, serving as an impactful instructional alternative to overcome learning difficulties in abstract physics topics.